2015
DOI: 10.1002/jbt.21724
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Responses of Human Hepatocytes to Emodin, Aristolochic Acid, and Triptolide: Chemicals Purified from Traditional Chinese Medicines

Abstract: The present study was undertaken to investigate the metabolic responses of human liver cells HL-7702 on chemicals purified from traditional Chinese medicine: emodin, triptolide, and aristolochic acid. Cytotoxicity tests demonstrated a dose-dependent toxic effect of emodin, triptolide, and aristolochic acid on HL7702 cells for 48 h. Emodin (14 μM), aristolochic acid (12 μg/mL), or triptolide (18 nM) was individually administrated to HL7702 and cell samples were collected after 48 h for metabolites extraction an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Analysis of serum samples from rats in the control and emodin groups indicated that emodin induced liver injury (Yang et al, 2018). Previous studies have also found that emodin induced liver injury in vivo and in vitro to some extent (Li et al, 2012;Zhang et al, 2010;Liu et al, 2015b;Ma et al, 2015;Jiang et al, 2017), similar to our observation.…”
Section: Discussionsupporting
confidence: 91%
“…Analysis of serum samples from rats in the control and emodin groups indicated that emodin induced liver injury (Yang et al, 2018). Previous studies have also found that emodin induced liver injury in vivo and in vitro to some extent (Li et al, 2012;Zhang et al, 2010;Liu et al, 2015b;Ma et al, 2015;Jiang et al, 2017), similar to our observation.…”
Section: Discussionsupporting
confidence: 91%
“…Elevated levels of metabolites from these groups are associated with altered fatty acid oxidation/metabolism and disease. [30][31][32] Analysis of the fecal metabolome by GC/LC-MS separated patients with IBS from control individuals ( Figure 3C), again without difference among the clinical IBS subtypes ( Supplementary Figure 7). Machine learning identified 158 fecal metabolites predictive of IBS (AUC, 0.686; sensitivity, 0.737; specificity, 0.476) ( Supplementary Table 7), which included the amino acids L-alanine, L-arginine, tyrosine, Lphenylalanine; dodecanedioic acid, an indicator of fatty acid oxidation defects, 33 and 2 purine nucleosides, adenosine and inosine, previously reported as biomarkers of IBS.…”
Section: Altered Urine and Fecal Metabolomes In Irritable Bowel Syndromementioning
confidence: 88%
“…However, these changes exhibited opposite trends in the DSS vs. LB-DSS comparison. The N1-acetylspermidine metabolites, which are related to amino acid metabolism and oxidative stress in cells, are polyamines derived from ornithine and methionine and play an important role in cell membrane stability, biosynthesis of signaling molecules, and cell growth and differentiation (Ramot et al, 2010; Liu et al, 2015). Arachidonic acid is the main precursor of eicosanoid mediators, and the abundance of this metabolite is greatly increased after cell activation (Calder, 2011).…”
Section: Discussionmentioning
confidence: 99%